Nigella sativa: A Dietary Supplement as an Immune-Modulator on the Basis of Bioactive Components - Niu, Yun; Wang, Baoguang; Zhou, Li; Ma, Changyang; Waterhouse, Geoffrey I. N.; Liu, Zhenhua; Ahmed, Adel F.; Sun-Waterhouse, Dongxiao; Kang, Wenyi (Frontiers in Nutrition, 2021)
Nutrients that can be considered as functional foods and exert physiological benefits on immune system. The seeds of Nigella sativa with many active constituents are mainly used for medicine, food spice and nutritional supplements in Egypt. Much attention has been paid to N. sativa seeds for their anticancer, antibacterial, anti-inflammatory and immune properties. However, it is unclear that active constituents and mechanisms underlying functions from N. sativa seeds. Thus, the bioactive constituents with immune regulation from N. sativa seeds were systematically studied. A new compound (3-methoxythymol-6-O-β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside 1) and eleven known compounds (2-12) were separated from the N. sativa seeds by chromatographic methods. Their structures were elucidated by spectroscopic analysis of MS, UV, IR, 1H- and 13C-NMR. Furthermore, immunomodulatory effects of those compounds in RAW 264.7 cells were evaluated by phagocytosis, NO and cytokine release, related mRNA transcription and key proteins expression in vitro. Monosaccharide derivatives, Ethyl-α-D-furaarabinose (5) and Ethyl-β-D-fructofuranoside (8), played a bidirectional regulatory role in immunity and anti-inflammation through regulating NF-κB signaling pathways. The results showed that active compounds and the mechanism of immune regulation in N. sativa, it indicated that N. sativa seeds could be used as dietary supplements in immunomodulation.